Foundation physics - Gibb, Keith; Hutchings, Robert (United Kingdom : Cambridge, 1997)
Foundation Physics provides an introduction to the fundamental concepts in advanced physics. It contains material from the new A level common core that covers physical quantities and units, Newton's laws of motion, work and energy, waves, DC electricity and atomic structure.
Includes index.
Keywords: Physics